Oxygenation and Hemodynamic Changes in Traumatic Brain Injury: A Literature Review - Firdaus, Riyadh; Aida Rosita Tantri (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Traumatic brain injury (TBI) is a major public health problem and the main cause of death and disability worldwide. TBI can causing primary and secondary injury. Primary brain injury occurs within a moment after a collision and worsen by acute systemic damage such as hypoxia, bleeding, and neurotoxic pathway activation. Under normal conditions, brain has several mechanisms for regulating pressure and volume to prevent ischemia. The purpose of these mechanisms is to maintain a continuous cerebral blood flow (CBF) and adequate oxygen supply.